Bruksisma Bruxism - Sri Wendari A. Hartono; Nunung Rusminah; Aprillia Adenan (DiscoverSys Inc., 2011)
This paper reviewed of bruxism phenomenon that refers to the grinding or clenching of the teeth during awake ornight sleep. The prevalence of bruxism decreases with age from 14-18% in childhood, 8% of adult population and3% in the elderly. According to the existing literature, two groups of proposed etiological factors can bedistinguished: peripheral (morphological) and central (pathophysiological and psychological). At present, thebruxism is more often thought to be regulated centrally, not peripherally. Signs and symptoms of bruxism such astooth wear/dental attrition, abfractions, orofacial pain, change of periodontal ligament, mobility, tooth sensitivity,fractured teeth and fillings, earache, headache, tightness of jaw muscle, chewed tissue on the inside of your cheek,impact on the esthetic appearance of a smile. There have been many clinical approaches to the treatment ofbruxism. These can be categorized as acute, preventive and chronic management of bruxism, based on patient’ssigns and symptoms. In the case of acute symptoms with patients experiencing pain, pharmaco-therapeutics may berequired. Meanwhile, if tooth wear is present an occlusal splint and stress management are recommended. Dentistsand health professionals should be aware of increasing the phenomenon of bruxism.